Finger Jointed Timber from Plantation Species Using Indigenous Machines - Uday, N. D.; Mathews, K. C.; Mohandas, K. K.; Jagadish, H. N.; Bansal, A. K. (Indian Forester, 2005)
The technology of finger-jointing of plantation grown timbers for producing bigger sizes is gradually gaining momentum in the country. One of the constraints in this process is the high cost of imported finger-jointing machines. Recently, the Building Materials & Technology Promotion Council (BMTPC), New Delhi, an inter-ministerial organization of the Government of India has developed finger-jointing machines which were installed at indian plywood Industries Research and Training Institute (lPIRTI), Bangalore for research and training purposes. At IPIRTI a study was carried out to evaluate the strength of finger-jointed timber produced from plantation grown species viz. Gravellia robusta (Silver oak), Eucalyptus tereticornis, (Eucalyptus) and Havea brasiliensis (Rubber wood). it was found that fingerjointed timbers from plantation species have strength in the range of 60-73% of defect free solid timber from- the respective species.